How low can we (reliably) go? A method comparison of thyroid-stimulating hormone assays with a focus on low concentrations - Stan R Ursem; Anita Boelen; Jacquelien J Hillebrand; Wendy P J den Elzen; Annemieke C Heijboer (European Thyroid Journal, 2023)
Objective: International guidelines concerning subclinical hyperthyroidism and thyroid cancer advice absolute cut-off values for aiding clinical decisi ons in the low range of thyroid-stimulating hormone (TSH) concentrations. As TSH assays are known to be poorly standardized in the normal to high range, we performed a TSH assay method comparison focusing on the low range. Methods: Sixty samples, selected to cover a wide range of TSH concentrat ions (<0.01 to 120 mIU/L) with oversampling in the lower range (<0.4 mIU/L) , were used for the method comparison between three TSH immunoassays (Cobas, Alinit y and Atellica). In addition, 20 samples were used to assess the coefficient of va riation from duplicate measurements in these three methods. Results: The TSH immunoassays showed standardization differences with a b ias of 7–16% for the total range and 1–14% for the low range. This cou ld lead to a different classification of 1.5% of all measured TSH concentrations <0.40 mIU/L measured in our laboratory over the last 6 months, regarding the clinically imp ortant cut-off value of TSH = 0.1 mIU/L. As the imprecision of the immunoassays varied from 1.6–5.5%, this could lead to a similar reclassification as the bias between imm unoassays. Conclusions: We established the standardization differences of frequently used TSH assays for the total and low concentration ranges. Based on the proportional bias and the imprecision, this effect seems to have limited clinical consequences for the low TSH concentration range. Nevertheless, as guidelines mention absolute TSH values to guide clinical decision-making, caution must be applied when interpreting values close to these cut-offs.